Zillennials, Social Media and Artificial Intelligence: A Survey on West Java’s Digital Natives - Vidi Sukmayadi; Sarah Annisa Fadhila; Ira Mirawati; Melly Maulin Purwaningwulan; Enjang Muhaemin (Ikatan Sarjana Komunikasi Indonesia, 2024)
Today’s rapid digital and artificial intelligence development has a significant impact on the lives of generation Z, also known as Zillennials. This study is part of the research initiative taken by the Indonesian Association of Communications Scholars of West Java Region (ISKI Jabar) , and aims to identify and map trends in the usage of social media and artificial intelligence among the region's Zillennials. The survey was conducted on 515 respondents aged 12-27 years, covering aspects of device utilization, intensity of internet and social media use, and perceptions of AI. Based on the study's findings, West Java Zillennials had a high level of device ownership and internet usage intensity, reaching 93% with an average daily duration of 5-6 hours. Instagram, TikTok, and Twitter have emerged as the primary social media platforms for Generation Z, substituting Facebook's previous supremacy. The integration of AI, particularly Google Assistant and ChatGPT, is increasingly becoming prevalent in everyday life, mostly employed to assist with work and academic assignments, as well as for information retrieval. Although most Zillennials display excitement towards the utilization of AI, their technical comprehension of AI classifications and functionalities remains restricted. The findings have significant implications for understanding the influence of technology on the lives of Zillennials. They also emphasize the importance of enhancing media literacy skills to properly embrace the digital and artificial intelligence era.